Preparation method of copper-nickel alloy electrode and method for driving CO2 electrocatalytic reduction to prepare wide-ratio synthetic gas

CN121344656BActive Publication Date: 2026-10-27HARBIN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511487692.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-10-17
Publication Date
2026-10-27
Estimated Expiration
2045-10-17

AI Technical Summary

Benefits of technology

本发明提供的双金属铜镍合金催化剂的比例容易调控,具体可以通过控制前驱体中铜离子和镍离子的摩尔比例调控合金中铜镍元素比,从而实现了对其催化活性位点和CO2催化性能的调控。铜与镍形成合金后,由于镍的电负性比铜强,合金界面处存在从铜向镍的电子转移。这一电子重排效应导致铜的d带中心下移,进而调控了其对关键反应中间体的吸附强度。具体表现为:适度削弱了COOH中间体的吸附能,降低了CO2活化转化为CO的能垒(体现为起始电位降低);同时,也优化了CO中间体的吸附能,使其既能稳定生成又易于脱附,有效抑制了*CO的进一步加氢还原,从而显著提高了CO产物的选择性(法拉第效率可达78%以上)。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121344656B_ABST
    Figure CN121344656B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a copper-nickel alloy electrode and a method for driving CO2 electrocatalytic reduction to prepare a wide-ratio synthesis gas, and belongs to the field of CO2 electrocatalytic reduction.The molar ratio of copper ions and nickel ions in a precursor is controlled to regulate the copper-nickel element ratio in the alloy, so that the catalytic active sites and the CO2 catalytic performance are regulated.After copper and nickel form an alloy, because the electronegativity of nickel is stronger than that of copper, there is an electron transfer from copper to nickel at the alloy interface.This electron rearrangement effect causes the d-band center of copper to move downward, and further regulates the adsorption strength of a key reaction intermediate.The application moderately weakens the adsorption energy of a COOH intermediate, reduces the energy barrier of the conversion of CO2 into CO (reflected in the reduction of the initial potential), and simultaneously optimizes the adsorption energy of a CO intermediate, so that the CO intermediate can be stably generated and easily desorbed, the further hydrogenation reduction of the CO intermediate is effectively inhibited, and the selectivity of the CO product is significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of CO2 electrocatalytic reduction, specifically, it relates to a method for preparing a copper-nickel alloy electrode and a method for producing a wide-ratio syngas by driving CO2 electrocatalytic reduction using a copper-nickel alloy electrode. Background Technology

[0002] Currently, the continuous increase in CO2 emissions has driven in-depth research on the resource utilization of CO2. Electrocatalytic reduction of CO2 (ECO2RR) technology can convert CO2 into high-value-added chemicals and fuels. Syngas (H2 / CO), as a key chemical feedstock, is widely used in the production of methanol, ammonia, and many other bulk chemicals. Compared with traditional fossil fuel-dependent processes, the electrocatalytic route has potential advantages such as cleaner processes and milder operating conditions, making it significant for developing low-cost, high-efficiency syngas production technologies.

[0003] Under the "dual carbon" objective, the preparation of syngas using ECO2RR has become a research hotspot and an important pathway. However, this reaction process involves multiple electron transfers, resulting in complex products and low selectivity for the target product. Therefore, developing high-performance catalytic electrode materials is a core challenge.

[0004] Currently, the core challenge facing the technology of producing syngas (H2 / CO) using CO2 electrocatalysis lies in the difficulty of effectively controlling and improving the selectivity of the target product. This "selectivity limitation" problem manifests itself in the following ways: First, the CO2 reduction process itself involves multiple parallel reaction pathways, and its final products are complex. In addition to the target carbon monoxide (CO), it often produces various hydrocarbons such as formic acid, methanol, methane, and even ethylene and ethanol, which severely disperses the selectivity of the reaction for syngas. Second, even if syngas is produced, the crucial H2 / CO ratio is extremely difficult to precisely control because the unavoidable hydrogen evolution reaction (HER) in aqueous phase electrolysis produces a large amount of hydrogen as a byproduct, and the adsorption strength of key intermediates (such as *CO) on the surface of the catalytic material directly affects the CO production efficiency and subsequent conversion, making it exceptionally difficult to achieve a wide range of predictable syngas output ratios. The purpose of this invention is to provide a bimetallic catalytic electrode material that, by precisely controlling the types, ratios, and microstructures of the two metal components, utilizes their electronic effects and synergistic catalytic interactions to efficiently and stably reduce CO2 to syngas. The key innovation lies in the ability to achieve a wide-range adjustable H2 / CO ratio through the rational design of the copper-nickel bimetallic catalyst, thereby meeting the specific feedstock gas requirements of various downstream chemical processes. This adjustability significantly improves the energy utilization efficiency and process economy of CO2, providing a novel and efficient solution for the electrocatalytic production of syngas.

[0005] This invention presents a method for preparing a copper-nickel alloy catalyst via hydrogen reduction. The reduction performance of the catalyst is controlled by adjusting the alloy structure and crystal facets. The reduction products are studied by applying an electrolytic voltage to the catalyst, thereby improving the Faraday efficiency and selectivity of the CO gaseous products. In an electrolyte solution, the prepared copper-nickel alloy catalyst is coated onto carbon cloth as the working electrode to electrocatalytically reduce CO2, yielding CO and H2 products. This provides a concrete application example for the electrocatalytic reduction of CO2 to produce syngas (H2 / CO).

[0006] To address the aforementioned technical problems, the present invention adopts the following technical solution: I. The purpose of this invention is to provide a method for preparing bimetallic copper-nickel alloys. In the copper-nickel alloy catalyst prepared by this invention, the molar ratio of copper to nickel is 1:1, 1:2, and 2:1, respectively.

[0007] 1. Configure copper-nickel precursors 0.15–0.52 g Ni(NO3)2·6H2O and 0.11–0.52 g Cu(NO3)2·3H2O were dissolved in 20–70 mL H2O at room temperature to form a homogeneous solution A. 0.20–0.82 g citric acid (in excess) was dissolved in 10–50 mL H2O at room temperature to form a homogeneous solution B. After mixing solutions A and B, the mixture was sonicated for 10–50 min and then placed in a vacuum drying oven at 50–200 °C and vacuum dried at -0.05 MPa to -0.15 MPa for 8–20 h to obtain Cu / Ni alloy precursor powders with different proportions.

[0008] Reduction of copper-nickel catalyst The Cu / Ni precursor powders prepared in different proportions were placed in a muffle furnace and held at 300–500 °C for 1–7 h; subsequently, under H2 atmosphere protection, they were reduced at 200–700 °C for 1–5 h to obtain a black powder, which is the copper-nickel alloy catalyst. II. Preparation of Copper-Nickel Alloy Electrodes A catalyst solution was prepared by placing 2–8 mg of catalyst powder in 200–500 μL of isopropanol and 10–50 μL of 5 wt% Nafion solution. The catalyst solution was then ultrasonically treated for 10–50 minutes in an ultrasonic cleaner, and the solution was uniformly coated onto the treated carbon cloth using a pipette. The prepared electrode was dried at 10–80 °C for 2–8 h for later use.

[0009] III. Electrocatalytic Reduction of CO2 by Copper-Nickel Alloy Catalysts The prepared copper-nickel alloy electrode was used as the working electrode, and the Ag / AgCl electrode was used as the reference electrode. A two-chamber electrolytic cell system was assembled, and CO2 catalytic reduction tests were conducted in this system. The specific implementation steps are as follows: 1. Preparation of electrolyte The catholy solution is 30 mL of a 0.5 M KHCO3 solution. The anolyte is 30 mL of a 0.1 M dilute sulfuric acid solution.

[0010] 2. Electrocatalytic reduction of CO2 electrolysis test The CO2 electrolysis reaction was carried out in an H-type dual-chamber electrolytic cell. The cathode and anode of the electrolytic cell were separated by a Nafion 117 proton exchange membrane, allowing only protons to pass through. These protons provided the proton source for the reaction in the cathode region. The dried alloy catalyst electrode was used directly as the working electrode, the Pt electrode as the auxiliary electrode, and the Ag / AgCl electrode as the reference electrode. Before electrolysis, a certain amount of N2 was introduced into the cathode to purge the air, followed by continuous introduction of CO2 for 30 min to saturate the electrolyte. During electrolysis, the gas introduction was stopped to prevent bubbles generated during gas introduction from causing disturbance in the cathode chamber. After electrolysis at a constant potential for 60 min, the gaseous products were collected for analysis.

[0011] This invention prepares copper-nickel alloy catalysts with different proportions, which are further used for the electrocatalytic reduction of CO2 to produce syngas (H2 / CO). The reduction of CO2 in an ECO2RR reduction system using copper-nickel alloy materials is evaluated, and the reduction current density, the Faraday efficiency of the reduction product syngas (H2 / CO), and the selectivity are assessed.

[0012] Compared with the prior art, the present invention has the following beneficial effects: The bimetallic copper-nickel alloy catalyst provided by this invention has easily adjustable proportions. Specifically, the copper-nickel element ratio in the alloy can be controlled by adjusting the molar ratio of copper and nickel ions in the precursor, thereby achieving regulation of its catalytic active sites and CO2 catalytic performance. After copper and nickel form an alloy, due to the stronger electronegativity of nickel than copper, electron transfer occurs from copper to nickel at the alloy interface. This electron rearrangement effect causes the d-band center of copper to shift downward, thereby regulating its adsorption strength for key reaction intermediates. Specifically, it moderately weakens the adsorption energy of the COOH intermediate, lowering the energy barrier for CO2 activation to CO (manifested as a decrease in onset potential); at the same time, it also optimizes the adsorption energy of the CO intermediate, making it both stably formed and easily desorbed, effectively inhibiting further hydrogenation reduction of *CO, thus significantly improving the selectivity of CO products (Faraday efficiency can reach over 78%).

[0013] The bimetallic copper-nickel alloy solution provided by this invention has a simple and efficient process, uses water as a solvent for safety and environmental protection, and precisely prepares a highly active copper-nickel alloy catalyst through citric acid complexation and segmented heat treatment. It is easy to scale up production and has great application prospects.

[0014] This invention obtains a catalyst (Cu1Ni1) with high selectivity and stability by controlling the ratio of copper and nickel, and its electrocatalytic reduction potential for CO2 is only -0.08 (…). vs. RHE), at -0.08 ( vs. The Faraday efficiency of CO can reach a maximum of 78.13% when electrolyzed for 1 h at a voltage of RHE, and it remains high even at -0.38 ( vs. At the RHE voltage, a high current density (0.168 mA / cm²) can be maintained while ensuring a Faraday efficiency greater than 50%. 2 ).

[0015] The catalyst synthesized in this invention produces a syngas (H2 / CO) ratio in the ECO2RR reduction system of copper-nickel alloy materials ranging from approximately 0.25 to 47.52, exhibiting a wide range and high controllability.

[0016] For a deeper understanding of the features and technical content of this invention, please refer to the accompanying detailed description and drawings. It should be noted that the drawings are provided for illustrative purposes only and are not intended to limit the scope of the invention. Attached Figure Description

[0017] Figure 1 These are the X-ray powder diffraction patterns of the three copper-nickel alloy catalysts prepared. Figure 2 The image shows the SEM pattern of the prepared Cu1Ni1 catalyst. Figure 3 shows the cyclic voltammetry curves of the copper-nickel alloy electrode under N2 or CO2 saturation. Figure 4 shows the linear current-voltage (LSV) scan curves of the copper-nickel alloy electrode under N2 or CO2 saturation; Figure 5 shows the electrochemical impedance spectroscopy (EIS) curves of the copper-nickel alloy electrode under N2 or CO2 saturation. Figure 6 The it curve is the electrocatalytic reduction reaction of CO2 in an H-type dual-chamber electrochemical electrolytic cell with Cu1Ni1 alloy as the working electrode. Figure 7 The graph shows the product Faradaic efficiency and current density of Cu1Ni1 catalyst at different potentials. Figure 8 This is a comparison chart of the synthesis gas range of the three copper-nickel alloy catalysts prepared. Detailed Implementation

[0018] The present invention will be described in detail below with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, but should not be considered as limiting the present invention. It should be noted that those skilled in the art can make several modifications and improvements without departing from the concept of the present invention. These all fall within the protection scope of the present invention.

[0019] Example 1 (1) Preparation of Cu / Ni alloy precursor powder: 0.291 g Ni(NO3)2·6H2O and 0.242 g Cu(NO3)2·3H2O were dissolved in 40 mL H2O at room temperature to form a homogeneous solution A. 0.576 g citric acid (in excess) was dissolved in 20 mL H2O at room temperature to form a homogeneous solution B. Solutions A and B were mixed and sonicated for 20 min, then placed in a vacuum drying oven at 120 ℃ and vacuum dried at -0.09 MPa for 12 h to obtain Cu / Ni alloy precursor powder.

[0020] (2) Reduction by copper-nickel catalyst: The Cu / Ni precursor powder was placed in a muffle furnace and held at 400 °C for 4 h; then, it was reduced at 500 °C for 2 h under H2 atmosphere protection to obtain a black powder, which is the copper-nickel alloy catalyst.

[0021] The specific operational steps for using a copper-nickel alloy electrode for electrocatalytic CO2 reduction are as follows: Preparation of electrolyte: 1. Cathode electrolyte: Dissolve 1.5 g KHCO3 in 30 ml H2O to obtain the electrolyte, which is the catholyte. The concentration of KHCO3 in the solution is 0.5 M.

[0022] II. Anode electrolyte: Take 28.641 mL of deionized water and 1.359 mL of concentrated sulfuric acid and stir to mix to obtain a 0.1 M dilute sulfuric acid solution, which is the anolyte with a volume of 30 mL.

[0023] 2. Electrode fabrication using copper-nickel alloy catalyst supported on carbon cloth: I. Preparation of catalyst slurry: Place 5-6 mg of catalyst powder in 350 μL of isopropanol and 30 μL of... The slurry was ultrasonically treated in an ultrasonic cleaner for 30 min in a 5 wt% Nafion solution and the resulting dispersion could be used for electrode loading.

[0024] II. Catalyst loading and drying Use a pipette to take 10 μL of catalyst solution each time and spread it evenly on the treated carbon cloth (geometric area = 1 cm²). 2Ten samples were taken from a catalyst support (1cm x 1cm) and applied to it. The catalyst-coated carbon cloth was then placed at 60°C. o The copper-nickel alloy catalyst electrode can be obtained by drying at C.

[0025] The carbon cloth is treated with a two-step acid treatment method: first, it is soaked in a mixed acid of H2SO4 / HNO3 (volume ratio of 1:3) at room temperature for 10 hours, thoroughly washed with water and dried, and then refluxed with concentrated HNO3 at 100℃ for 2 hours, thoroughly washed with water and dried.

[0026] 3. Electrocatalytic reduction of CO2 using copper-nickel alloy catalysts The CO2 electrolysis reaction was carried out in an H-type two-chamber electrolytic cell. The cathode and anode of the electrolytic cell were separated by a Nafion 117 proton exchange membrane, allowing only protons to pass through. The protons provided the proton source for the reaction in the cathode region. The dried alloy catalyst electrode was used directly as the working electrode, the Pt electrode as the auxiliary electrode, and the Ag / AgCl electrode as the reference electrode. Before electrolysis, N2 was first introduced into the cathode to purge the air, and then CO2 was continuously introduced for 30 min to saturate the electrolyte. During electrolysis, the gas introduction was stopped to prevent bubbles generated by the gas introduction from causing disturbance in the cathode chamber. After electrolysis at a constant potential for 60 min, the liquid and gaseous products were collected for analysis. The gaseous products after the reaction were CO and H2, with no liquid products. The Faraday efficiency of the gaseous product CO ranged from 2.14% to 78.13%, with the highest syngas (H2 / CO) ratio being 47.52 and the lowest being 0.25.

[0027] Three alloy powders, Cu1Ni1, Cu1Ni2, and Cu2Ni1, were obtained using the method described in Example 1, with copper and nickel molar ratios of 1:1, 1:2, and 2:1, respectively.

[0028] X-ray powder diffraction was used to analyze three alloy powders: Cu1Ni1, Cu1Ni2, and Cu2Ni1. The results are as follows: Figure 1 As shown, all three samples, Cu1Ni1, Cu1Ni2, and Cu2Ni1, formed alloy solid solutions. Among them, Cu1Ni1 exhibited significantly higher diffraction peak intensities, indicating better crystallinity or higher phase purity. Furthermore, due to the change in lattice constant caused by the alloy composition, the diffraction peak positions of Cu1Ni2 and Cu2Ni1 showed clear shifts relative to Cu1Ni1, directly confirming the successful synthesis of alloys with different Cu / Ni ratios.

[0029] Figure 2 This is a SEM image of the freshly prepared Cu1Ni1 powder alloy catalyst. Before the reaction, the catalyst exhibits a typical irregular porous structure with uniform pore distribution and good connectivity. This high porosity effectively increases the contact area between the electrolyte and the catalyst surface, providing abundant contact channels for active sites of reactant molecules.

[0030] Figure 3 shows the cyclic voltammetry curves of three copper-nickel alloys with different ratios. In Figure 3, 3A represents the cyclic voltammetry curve of the prepared Cu1Ni1, 3B represents the cyclic voltammetry curve of the prepared Cu1Ni2, and 3C represents the cyclic voltammetry curve of the prepared Cu2Ni1. Figure 3 shows that the copper-nickel alloys with different ratios exhibit good electrochemical activity. Furthermore, comparing the current densities under N2 and CO2 atmospheres reveals that the current density of all three alloy catalysts is higher under a CO2 atmosphere than under a N2 atmosphere, indicating that all three synthesized alloys can effectively promote CO2 reduction. It is also evident that Cu1Ni1 has the highest current density, indicating its superiority in catalyst activity, electrode structure optimization, and electrolyte synergistic effect. This advantage not only improves the electrochemical reaction rate and stability but also demonstrates its application potential in ECO2RR.

[0031] Linear sweep voltammetry (LSV) curves were performed using three copper-nickel alloys as working electrodes, as shown in Figure 4. Figure 4A This represents the cyclic voltammetry curve of Cu1Ni1. Figure 4B This represents the cyclic voltammetry curve of Cu1Ni2. Figure 4C The cyclic voltammetry curves for Cu2Ni1 are shown in Figure 4. As can be seen from Figure 4, the cyclic voltammetry curves for Cu2Ni1 are within the voltage range of -0.58 to 1.1 V. vs. LSV scanning tests were performed on CO2-saturated Na2SO4 solution containing RHE. By comparing the LSV curves under different atmospheres, it was found that the current density of these catalyst materials in CO2-saturated electrolyte was higher than that in N2-saturated electrolyte, indicating that these three materials have better catalytic performance.

[0032] Using three copper-nickel alloys as working electrodes, electrochemical impedance spectroscopy (EIS) tests were performed, as shown in Figure 4. In Figure 4, 5A represents the EIS curve of Cu1Ni1, 5B represents the EIS curve of Cu1Ni2, 5C represents the EIS curve of Cu2Ni1, and 5D represents the EIS curves of the three catalysts prepared in Example 1 under a CO2 atmosphere. The EIS tests show that the CO2 atmosphere significantly reduces the charge transfer resistance of the catalysts, confirming its strong promoting effect on ECO2RR. Among them, the Cu1Ni1 catalyst exhibits the lowest charge transfer resistance, possessing optimal interfacial transport performance and reaction kinetics, which is the key reason for its high catalytic activity.

[0033] In an H-type two-chamber electrolytic cell, using a Cu1Ni1 alloy electrode as the working electrode, a series of constant voltages are applied to the system to perform constant potential electrolysis, yielding the It curve. For example... Figure 6As shown, the Cu1Ni1 catalyst exhibits good stability after 1 h of constant potential electrolysis within a specific voltage range, and the current density does not fluctuate significantly over time.

[0034] like Figure 7 As shown in the figure, the Faraday efficiency and current density of CO2 and H2 are displayed at different potentials when the Cu1Ni1 alloy electrode is used as the working electrode.

[0035] Figure 8 The graph shows a comparison of the syngas ratio at different potentials when the three copper-nickel alloys prepared in Example 1 are used as working electrodes. It can be seen that Cu1Ni1 has the widest syngas ratio.

[0036] The specific embodiments of the present invention have been described in detail above. It should be noted that the present invention is not limited to the specific embodiments described above. Various modifications or alterations can be made by those skilled in the art without departing from the scope of protection defined by the claims, and all such modifications or alterations fall within the scope of the present invention.

Claims

1. A method for preparing a copper-nickel alloy electrode, characterized in that, Includes the following steps: Step 1: Dissolve Ni(NO3)2·6H2O and Cu(NO3)2·3H2O in H2O to form a homogeneous solution A, and dissolve citric acid in H2O to form a homogeneous solution B; mix solutions A and B, sonicate, and dry to obtain Cu / Ni alloy precursor powder; Step 2: Then, keep the temperature at 300℃~500℃ for 1h~7h; subsequently, reduce the catalyst at 200℃~700℃ for 1h~5h under H2 atmosphere to obtain the catalyst. Step 3: Place the catalyst in isopropanol and Nafion solution, sonicate for 10 min to 50 min, coat it evenly on acid-treated carbon cloth, and dry it to obtain the copper-nickel alloy electrode. In the catalyst, the molar ratio of copper to nickel is 1:

1.

2. The method according to claim 1, characterized in that, Dissolve 0.20 g to 0.82 g of citric acid in 10 mL to 50 mL of H2O.

3. The method according to claim 1, characterized in that, 2 mg to 8 mg of catalyst were placed in 200 μL to 500 μL of isopropanol and 10 μL to 50 μL of 5 wt% Nafion solution.

4. The method according to claim 1, characterized in that, In step 1, vacuum drying is performed at 50 ℃~200 ℃ and -0.08MPa~-0.1MPa.

5. The method according to claim 1, characterized in that, Acid treatment: First, soak in a mixed acid with a volume ratio of H2SO4 / HNO3 of 1:3 at room temperature for 5 to 15 hours, wash thoroughly with water and dry, then reflux with concentrated HNO3 at 100°C for 2 hours, wash thoroughly with water and dry.

6. The method according to claim 1, characterized in that, In step 3, drying is carried out at 10 ℃ to 80 ℃.

7. A method for producing a wide-ratio syngas by electrocatalytic reduction of CO2 driven by a copper-nickel alloy electrode, characterized in that, The electrolysis is carried out in an H-type dual-chamber electrolytic cell. The copper-nickel alloy electrode prepared by the method of claim 1 is used as the working electrode, the reference electrode is an Ag / AgCl electrode, and the Pt electrode is the auxiliary electrode. The cathode and anode are separated by a Nafion 117 proton exchange membrane. The cathode solution is a KHCO3 solution, and the anode solution is a dilute sulfuric acid solution. Before electrolysis, N2 is first introduced into the cathode to purge the air, and then CO2 is continuously introduced to saturate the electrolyte. During the electrolysis process, the gas introduction is stopped, and the electrolysis is performed at a constant potential.

8. The method according to claim 7, characterized in that, The KHCO3 solution concentration is 0.5 M.

9. The method according to claim 7, characterized in that, The concentration of the dilute sulfuric acid solution is 0.1 M.